2020
DOI: 10.18502/kss.v4i6.6600
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Dark Tourism Experience among Visitors in Malaysia

Abstract: Tourists are continuously searching for new trends, exciting ways of traveling and a variety of adrenaline rush experiences. Dark tourism is one of many examples of tourism products that able to fulfill these objectives. Although Malaysia has many dark tourism sites, they are not globally recognized yet and able to attract international tourists. Many focused on the negative impacts of the sites rather than the potential benefits of the industry. Thus, this study is prepared to investigate the benefits of dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Among the dark tourism benefits, there is a high proportion of emotional and educational benefits (Chang, 2014; Oren et al , 2021). Jang (2021) and Zheng (2020) found that educational and learning benefits were the most pronounced, followed by strengthening family relationships and promoting positive moral values (Kang et al , 2012; Jamin et al , 2020). This investigation contends that perceived benefits can be divided into cognitive ones related to earthquake or related heritage information and knowledge, as well as affective benefits related to self, family, society and life perceptions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Among the dark tourism benefits, there is a high proportion of emotional and educational benefits (Chang, 2014; Oren et al , 2021). Jang (2021) and Zheng (2020) found that educational and learning benefits were the most pronounced, followed by strengthening family relationships and promoting positive moral values (Kang et al , 2012; Jamin et al , 2020). This investigation contends that perceived benefits can be divided into cognitive ones related to earthquake or related heritage information and knowledge, as well as affective benefits related to self, family, society and life perceptions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Initially, dark tourism was only related to death, fighting, and disasters. However, developments in the world of education, activities or behavior, and things that some people find strange, such as mysterious things, can be related to dark tourism (Jamin et al, 2020).…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Bisnis yang mengusung konservasi menjadi daya tarik tersendiri bagi wisatawan. Wisata jelajah dan kegiatan yang menguji adrenalin mulai banyak dilirik oleh wisatawan (Arquinez et al, 2020;Gracan, 2018;Jamin et al, 2020) terutama wisatawan muda.…”
unclassified
“…Pengembangan sumber daya alam sebagai obyek wisata harus didukung kelayakan obyek tersebut baik keselamatan, kenyamanan, keamanan (Giao et al, 2021) dan kemudahan untuk mengakses lokasi (Purnaya et al, 2019). Pelibatan masyarakat lokal sangat membantu sebagai tour guide dan keamanan (Jamin et al, 2020). Selain itu, Dampak negatif dari kunjungan wisatawan menjadi faktor penting untuk dipertimbangkan dalam pengembangannya (Kang, S., Zhang, X., & He, 2020;Laitamaki et al, 2016;Mudiana et al, 2020) Obyek wisata dipastikan tidak dibangun melebihi ambang batasnya (Trukhachev, 2015) yang dapat mempengaruhi ekosistemnya.…”
unclassified